PUBLIC RELATIONS IN THE IMPLEMENTATION OF THE PPEPP CYCLE IN FULFILLING NATIONAL EDUCATION STANDARDS IN MADRASAH - Maulidatul Adzimah; Siti Nur Aviatun Hasanah; Ittaqillah Haitsuma Kunta; Najiburrahman (Evaluasi : Jurnal Manajemen Pendidikan Islam, 2026)
The role of public relations in implementing the PPEPP cycle from the planning stage to the improvement stage to meet the National Education Standards analyzes the strategic role played by madrasah public relations. The type of research uses a qualitative approach, a case study type with data collection methods through observation, interviews, and documentation. The research subjects were the madrasah principal, Deputy Head of Public Relations, teachers and students. The results of the study show that at the planning stage the role of public relations is apparent through the process of identifying information and preparing communication patterns that are in line with the institution's quality policy. In the implementation stage, public relations plays a role in coordination between sectors so that information about the quality program is conveyed accurately. In the evaluation and control stage, public relations responses are collected and documentation related to public relations activities is recorded. In the improvement stage, public relations activities are evident through madrasah publications, documentation, and strengthening public trust in the madrasah. The PPEPP process involves public relations providing encouragement for quality management. These findings indicate that public relations plays a strategic role in ensuring educational quality so that efforts to meet the National Education Standards continue to develop and remain consistent.